Project Report on Fall Detection and Alert System for Elderly People - NILIMA PATHAK, SAHANA B V and SHRAVANTHI (2013)
INTERNAL GUIDE: MEERA K S, MVJCE EXTERNAL GUIDE: HARESH DAGALE, SENIOR SCINTIFIC OFFICER, DESE, IISC
Keywords: Alert System for Elderly People